Effects of bile acids on neurological function and disease. Issue 11 (28th July 2016) - McMillin, Matthew; DeMorrow, Sharon
ABSTRACT: Bile acids are synthesized from cholesterol and are known to be involved with the emulsification and digestion of dietary lipids and fat‐soluble vitamins. Outside of this role, bile acids can act as cell signaling effectors through binding and activating receptors on both the cell membrane and nucleus. Numerous reports have investigated these signaling pathways in conditions where the liver is damaged. More recently, effort has been made to investigate the role of bile acids in diseases out side of those associated with liver damage. This review summarizes recent findings on the influences that bile acids can exert in normal neurological function and their contribution to diseases of the nervous system, with the intent of highlighting the role of these metabolites as potential players in neurological disorders.—McMillin, M., DeMorrow, S. Effects of bile acids on neurological function and disease. FASEB J. 30, 3658–3668 (2016) www.fasebj.org